DHT-based functionalities using hypercubes - Alvarez Hamelin, José I. (2006)
Decoupling the permanent identifi er of a node from the node's topology-dependent address is a promising approach toward completely scalable self-organizing networks. Existing solutions use a logical tree-like structure that, although allowing for simple address assignment and management, lead to low route selection flexibility. This clearly results in low routing performance and poor resilience to failures. In this paper, we propose to increase the number of candidate paths by using incomplete hypercubes. We will see that this solution can cover a wide range of applications by adapting to the dynamics of the network